2022
DOI: 10.1017/s0022215121004400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mastoid and middle-ear volume on graft success and hearing outcomes in paediatric tympanoplasty

Abstract: Objective To examine the effects of mastoid and middle-ear volume on the anatomical and functional success of type 1 tympanoplasty in paediatric patients. Methods This study included 45 paediatric patients who underwent type 1 cartilage tympanoplasty. Patients’ demographic data, pre- and post-operative audiological evaluation results, and post-operative graft status were evaluated. Middle-ear and mastoid cavity volumes were calculated (in cubic centimetres) using temporal bone high-resolution computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…When planning middle ear surgery, including cochlear implantation, facial nerve decompression, ossiculoplasty, and tympanoplasty, among others (17), it is necessary to consider the size and growth of the mastoid air cells. The poor results of tympanoplasty in children may be due to immature mastoids (18,19). In addition, it has been reported that the degree of mastoid pneumatization is related to the degree of nasal septal deviation, eustachian tube length, tinnitus, presbycusis, cholesteatoma, cystic fibrosis, and other unknown conditions (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…When planning middle ear surgery, including cochlear implantation, facial nerve decompression, ossiculoplasty, and tympanoplasty, among others (17), it is necessary to consider the size and growth of the mastoid air cells. The poor results of tympanoplasty in children may be due to immature mastoids (18,19). In addition, it has been reported that the degree of mastoid pneumatization is related to the degree of nasal septal deviation, eustachian tube length, tinnitus, presbycusis, cholesteatoma, cystic fibrosis, and other unknown conditions (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Increased pneumatization of the temporal bone is associated with an improved prognosis in otitis media with effusion (OME) [ 13 ], as well as higher tympanoplasty graft success rates [ 14 ]. It is also relevant to surgical planning for bone conduction implants, active middle ear implants, and even cochlear implantation when assessing the space required for implant placement or predicting access to the middle ear via trans-mastoid, retro-facial approaches [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, temporal bone pneumatization positively correlates with the risk of OM with effusion and tympanoplasty success rates (Sade & Fuchs, 1997;Baklaci et al, 2022). It could also give favorable positioning of related vasculatures, such as the SS and JB, that could become pitfalls for surgeons (Friedman et al, 2010;.…”
Section: Justification Of Studymentioning
confidence: 99%